Foliar application of ascophyllum nodosum seaweed extract in soybeans for stress mitigation - Simonetti, Augusto Berleze; Furlan, Ana Eloísa; Bastos, Iago; dos Santos , Lusardo da Silva; da Silva, Ely Jhones Mello; Tabaldi, Luciane Almeri; Follmann, Diego Nicollau; Marques, Anderson Cesar Ramos (Disciplinarum Scientia | Naturais e Tecnológicas, 2026)
The use of seaweed extracts as biostimulants has emerged as a sustainable strategy to mitigate the effects of abiotic stresses in agricultural crops. The aim of this study was to evaluate the effects of foliar application of A. nodosum seaweed extract at different doses and application times, and how this product impacts the mitigation of stress caused by temperature and water scarcity.The experiment was conducted at the Federal University of Santa Maria in a completely randomized design with three treatments: control (0 L·ha⁻¹), 2 L·ha⁻¹ (recommended dose), and 4 L·ha⁻¹ (twice the recommended dose), applied at the V5-V6 and R1 growth stages. Growth, yield, and biochemical variables were evaluated, including total leaf area, grain yield, thousand grain weight, and the activity of antioxidant enzymes superoxide dismutase (SOD) and peroxidase (POD), as well as hydrogen peroxide (H₂O₂) content. The results showed no statistically significant differences in growth and yield variables. However, significant increases in H₂O₂ levels and SOD activity were observed in the seaweed extract treatments, indicating activation of the plant antioxidant defense system. These findings suggest that, although agronomic effects were not pronounced under the experimental conditions, A. nodosum extract induces biochemical responses associated with stress tolerance. Further studies with a higher number of replications, under different edaphoclimatic conditions and growth stages, are recommended to better assess the biostimulant’s effects.